Repel in two ticks - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
Tick-borne diseases are every cattle owner s nightmare. With redwater fever, heartwater, anaplasmosis and East Coast fever rampant, there is no (sub) tropical area in the world that is spared from these deadly tick-borne diseases. Various control...